Transformasi Praktik Mengajar Guru PAUD Setelah Mengikuti Program PKB Berbasis Lesson Study di TK Pautan Hati - Ramadhan, Salsabila; Utoyo, Setiyo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze in depth the transformation of teaching practices of Early Childhood Education (ECE) teachers at Pautan Hati Kindergarten after participating in the Continuous Professional Development Program (PKB) implemented through the Lesson Study model. This study uses a qualitative approach with a case study design. The subjects of the research are ECE teachers at Pautan Hati Kindergarten who actively participated in the Lesson Study-based PKB program. Data collection was conducted through participant observation, in-depth interviews, and analysis of lesson plans and teachers' reflective journals, both before, during, and after the intervention. Research findings indicate a significant positive transformation in teachers' teaching practices, including enhanced quality of child-centered lesson planning, more interactive and varied learning implementation, more authentic and formative assessment practices, and strengthened culture of collaboration and reflection among teachers. Factors such as teachers' motivation, support from school principals, and the quality of Lesson Study facilitation are the main supports for this transformation, while time and resource limitations serve as obstacles. The main conclusion emphasizes that Lesson Study-based professional development is effective in holistically transforming the teaching practices of early childhood education teachers.